2016
DOI: 10.4103/0974-2069.189122
|View full text |Cite
|
Sign up to set email alerts
|

Birth prevalence of congenital heart disease: A cross-sectional observational study from North India

Abstract: Objective:To assess the birth prevalence and pattern of congenital heart disease (CHD) using echocardiography in babies born in a community hospital of North India.Methods:A cross-sectional observational study conducted over a period of 3 years. Newborns born over a specific 8-h period of the day were recruited in the study. They underwent routine clinical examination and pulse oximetry, followed by screening echocardiography for diagnosing a CHD.Results:A total of 20,307 newborns were screened, among which 87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 20 publications
(21 reference statements)
5
56
0
2
Order By: Relevance
“…The present study on Sickneonates we observed a prevalence rate of 26 % which seems higher than other studies but may be explained by inclusion of more sick neonates We observed VSD in 28.2 percent of cases followed closely by ASD in about 21 % of cases VSD PDA 19.8 and PDA alone in 9.9 % of cases in sharp contrast to earlier study by Saxena et all who observed. [1][2][3]17] VSDs (restrictive and non restrictive) were the most common significant CHDs (43.9% and 20.7%, respectively) with a prevalence rate of 5.22 per 1000 live births. ASDs and PDAs consisted of 7.3% and 4.3% of the significant CHDs, with a prevalence rate of 0.59/1000 and 0.34/1000, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The present study on Sickneonates we observed a prevalence rate of 26 % which seems higher than other studies but may be explained by inclusion of more sick neonates We observed VSD in 28.2 percent of cases followed closely by ASD in about 21 % of cases VSD PDA 19.8 and PDA alone in 9.9 % of cases in sharp contrast to earlier study by Saxena et all who observed. [1][2][3]17] VSDs (restrictive and non restrictive) were the most common significant CHDs (43.9% and 20.7%, respectively) with a prevalence rate of 5.22 per 1000 live births. ASDs and PDAs consisted of 7.3% and 4.3% of the significant CHDs, with a prevalence rate of 0.59/1000 and 0.34/1000, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Khalil et al (15) 1994 Indian Pediatrics Hospital Live births 10964 3.9/1000 Kapoor R et al (9) 2007 Indian Pediatrics Hospital (Kanpur) 0-15 yrs. 10641 26/1000 M Mishra (16) 2009 IHJ Community (UP) 5-15 yrs. 118212 1.3/1000 Bhat NK (17) 2013 Indian journal of Pediatrics Hospital (Uttarakhand) 0-18 yrs.…”
Section: Chd Detected Bymentioning
confidence: 99%
“…Cardiac septal defects (CSDs) constitute 1% of all congenital heart diseases (CHDs) [1]. The prevalence of CHD worldwide (population based) is between 1 and 150/1000 live births, while in India, it is 8.07/1000 live births [2]. However, septal defects have a reported frequency of 4.1/1000 live births.…”
Section: Introductionmentioning
confidence: 99%